Adiponectin plays a protective role in caerulein-induced acute pancreatitis in mice fed a high-fat diet. Issue 10 (25th June 2008) - Araki, H; Nishihara, T; Matsuda, M; Fukuhara, A; Kihara, S; Funahashi, T; Kataoka, T R; Kamada, Y; Kiyohara, T; Tamura, S; Hayashi, N; Shimomura, I
Abstract : Background: Obesity is a risk factor for acute pancreatitis (AP), but the molecular mechanism remains unclear. Adiponectin, an adipose tissue-derived secretory factor, has anti-inflammatory properties in addition to various biological functions, and its plasma concentrations are reduced in obese subjects. However, the role of adiponectin in AP has not been investigated. Aim: To determine the effects of adiponectin on AP. Methods: We investigated the effects of adiponectin on experimental AP by using adiponectin-knockout (APN-KO) mice and adenovirus-mediated adiponectin over-expression. AP was induced by 10 hourly intraperitoneal injections of low-dose caerulein (10 μg/kg) after 2 week feeding of normal chow or a high-fat diet (HFD) in wild-type (WT) and APN-KO mice. We evaluated the severity of AP biochemically and morphologically. Results: Low-dose caerulein treatment did not induce pancreatic damage in either WT or APN-KO mice under normal chow feeding. APN-KO mice, but not WT mice, fed a HFD and then treated with caerulein developed pancreatic damage and inflammation, accompanied by increased macrophage/neutrophil infiltration and upregulation of pro-inflammatory mediators such as tumour necrosis factor α in the pancreas. Adenovirus-mediated over-expression of adiponectin attenuated the severity of HFD/caerulein-induced AP in APN-KO mice. Conclusions: Adiponectin plays a protective role in caerulein-induced AP in HFD-fed mice.